Early Predictors of the Long‐term Response to Therapy in Patients With Crohn Disease Derived From a Time‐Intensity Curve Analysis After Microbubble Contrast Agent Injection. (12th September 2018) - Quaia, Emilio; Gennari, Antonio Giulio; Cova, Maria Assunta
Abstract : Objectives: The aim of this study was to identify early predictors of the long‐term response to therapy in patients with Crohn disease (CD) from time‐intensity curves obtained after microbubble injection. Methods: One hundred fifteen consecutive patients with a proven diagnosis of CD involving the terminal ileal loop who were scheduled to begin pharmacologic therapy with biologics (infliximab or adalimumab) were scanned after sulfur hexafluoride–filled microbubble injection before the beginning and at the end of the sixth week of treatment. The absolute value and percentage change of each semiquantitative kinetic parameter (peak enhancement, time to peak enhancement, rise time, mean transit time, wash‐in and wash‐out rates, area under the curve [AUC] for the whole time‐intensity curve, AUC during wash‐in, AUC during wash‐out, and wash‐in perfusion index) as measured on the terminal ileal tract and adjacent reactive mesenteric fat were calculated from time‐intensity curves. Patients were followed for at least 24 months with redetermination of the Crohn Disease Activity Index and with at least 1 endoscopy within 18 weeks after the beginning of pharmacologic treatment. The absolute values and percentage changes of kinetic parameters were assessed as potential predictors of the therapeutic outcome by a logistic regression analysis. Results: The study group included 66 male and 49 female patients (mean age ± SD, 45.76 ± 11 years). The pretreatment values and percentage changes of the peak enhancement, AUC, AUC during wash‐in, and AUC during wash‐out were found to be predictors ( P < .05) of the long‐term therapeutic outcome. Conclusions: The analysis of time‐intensity curves obtained after microbubble contrast agent injection provides early predictors of the long‐term therapeutic outcome in patients with CD.